Pleurotus spp. Mycelia Enriched in Magnesium and Zinc Salts as a Potential Functional Food - Włodarczyk, Anna; Krakowska, Agata; Sułkowska-Ziaja, Katarzyna; Suchanek, Małgorzata; Zięba, Piotr; Opoka, Włodzimierz; Muszyńska, Bożena (Molecules (Basel, Switzerland), 2020)
Worldwide, mushrooms belonging to the Pleurotus spp. such as P. citrinopileatus, P. djamor, and P. pulmonarius are highly valued not only for their taste and aroma but also for their health-promoting properties. These species are rich in bioelements, vitamins, and above all, compounds that exhibit immunostimulatory activity. Therefore, in this study, we aimed to determine the effect of the supplementation of culture media using inorganic Mg and Zn salts. This is the first study to establish the bioavailability of the selected elements (Mg and Zn) and anions (Cl−, SO42−) from the enriched biomass by means of the extraction of lyophilized mycelium into artificial digestive juices. The following salts were added to the liquid Oddoux medium: ZnSO4·7H2O, ZnCl2, MgSO4·7H2O or MgCl2·6H2O. The bioelements, anions and organic compounds in the obtained biomass were determined. The addition of Zn and Mg salts to the media increased the production of biomass by 30% and increased the bioaccumulation of the inorganic salts. Maintaining in vitro cultures under optimized and controlled conditions produced mycelium with a better composition and health properties than otherwise. Such enriched biomass may be classified as potential functional foods, aiding in overcoming deficiencies of elements and organic compounds with biological activity in humans.